Intercoder Reliability and Validity of WebPlotDigitizer in Extracting Graphed Data. (March 2017) - Drevon, Daniel; Fursa, Sophie R.; Malcolm, Allura L.
Quantitative synthesis of data from single-case designs (SCDs) is becoming increasingly common in psychology and education journals. Because researchers do not ordinarily report numerical data in addition to graphical displays, reliance on plot digitizing tools is often a necessary component of this research. Intercoder reliability of data extraction is a commonly overlooked, but potentially important, step of this process. The purpose of this study was to examine the intercoder reliability and validity of WebPlotDigitizer (Rohatgi, 2015), a web-based plot digitizing tool for extracting data from a variety of plots, including XY coordinates of interrupted time-series data. Two coders extracted 3, 596 data points from 168 data series in 36 graphs across 18 studies. Results indicated high levels of intercoder reliability and validity. Implications of and recommendations based on these results are discussed in relation to researchers involved in quantitative synthesis of data from SCDs.